Future changes in North Atlantic winter cyclones in CESM-LE – Part 1: Cyclone intensity, potential vorticity anomalies, and horizontal wind speed - Dolores-Tesillos, Edgar; Teubler, Franziska; Pfahl, Stephan (EGU, 2022)
Strong low-level winds associated with extratropical cyclones can have substantial impacts on society. The wind intensity and the spatial distribution of wind maxima may change in a warming climate; however, the involved changes in cyclone structure and dynamics are not entirely clear. Here, such structural changes of strong North Atlantic cyclones in a warmer climate close to the end of the current century are investigated with storm-relative composites based on Community Earth System Model Large Ensemble (CESM-LE) simulations. Furthermore, a piecewise potential vorticity inversion is applied to associate such changes in low-level winds to changes in potential vorticity (PV) anomalies at different levels. Projected changes in cyclone intensity are generally rather small. However, using cyclonerelative composites, we identify an extended wind footprint southeast of the center of strong cyclones, where the wind speed tends to intensify in a warmer climate. Both an amplified low-level PV anomaly driven by enhanced diabatic heating and a dipole change in upper-level PV anomalies contribute to this wind intensification. On the contrary, wind changes associated with lower- and upper-level PV anomalies mostly compensate for each other upstream of the cyclone center. Wind changes at upper levels are dominated by changes in upper-level PV anomalies and the background flow. Altogether, our results indicate that a complex interaction of enhanced diabatic heating and altered non-linear upper-tropospheric wave dynamics shape future changes in near-surface winds in North Atlantic cyclones.